Recombinant Anti-Thrombin Production from Saccharomyces Cerevisiae: Large Scale Trends Based on Computational Predictions (2020)
Anti-thrombin III is a protein performing anticoagulant function by preventing coagulation process and currently it is used in critical Covid-19 patients. In the present research, recombinant anti-thrombin production at large scale is simulated using SuperPro Designer. Special emphasis was analysed for the elucidation of required unit operation at industrial scale. Saccharomyces cerevisiae yeast is fed with 50 g/L carbon source together with 1.9 g/L amino acids and 6.7 g/L nitrogenous yeast base. All yields are taken from current references. The process is divided in two stages: upstream and downstream. In upward flow a total 11.2 g/L of biomass is calculated. Subsequently, anti-thrombin extraction and purification strategies are proposed. Interestingly, a purified anti-thrombin protein is obtained at 312 mg/L. Based on the latter, the large scale plant proposed in this research can reach 26 vials/hour produced at a concentration of 250 mg. Also productivity and prefeasibility are evaluated and annual production of 205,920 anti-thrombin vials is calculated. Therefore, each vial has a production cost of 180 USD. Based on the authors knowledge, information regarding antithrombin large scale trends are scarce. That is why this is the motivation of this research to perform a computational estimate for the large scale operations involved for the anti-thrombin production.